Practical Methods of Teaching Music Lessons - Rustamjonova Dilkhavas Ravshvnbek qizi (International Journal on Orange Technologies, 2023)
We noted above that practical methods include exercises. In their implementation, not only verbal or visual perception of educational information takes place, but also direct application of the acquired theoretical knowledge in practice. It is very important to choose a system of exercises that allows you to fully apply the theoretical knowledge gained in practice when using the method of practical exercises.